Is it True That the Normal Valence‐Length Correlation Is Irrelevant for Metal–Metal Bonds?. Issue 15 (1st March 2016) - Singh, Vijay; Dixit, Mudit; Kosa, Monica; Major, Dan Thomas; Levi, Elena; Aurbach, Doron
Abstract: The most intriguing feature of metal–metal bonds in inorganic compounds is an apparent lack of correlation between the bond order and the bond length. In this study, we combine a variety of literature data obtained by quantum chemistry and our results based on the empirical bond valence model (BVM), to confirm for the first time the existence of a normal exponential correlation between the effective bond order (EBO) and the length of the metal–metal bonds. The difference between the EBO and the formal bond order is attributed to steric conflict between the (TM) n cluster (TM=transition metal) and its environment. This conflict, affected mainly by structural type, should cause high lattice strains, but electron redistribution around TM atoms, evident from the BVM calculations, results in a full or partial strain relaxation. Abstract : It's not true ! Existence of a normal exponential correlation between the effective bond order and the length of the metal–metal bonds was confirmed for the first time by a combination of available quantum chemistry data and calculations based on the empirical bond valence model. The difference between the effective and formal bond orders is assigned to steric conflict between the (TM) n cluster (TM=transition metal) and its environment.